Ketika perempuan lantang menentang poligami; Sebuah analisis wacana kritis tentang wacana antipoligami - Yuwono, Untung (Wacana, Journal of the Humanities of Indonesia, 2008)
Critical discourse analysis (CDA) has become a very influential interdisciplinary approach, which views a discourse as a form of social practice. Antipoligamy discourse, as a social practice persisted for a long time ago in Indonesia, offers chalenging discussions in the perspective of CDA. Teun van Dijk, as one of the pioneers of CDA, articulates ideology as the basis of the social representations of groups. Furthermore, he advocates a sociocognitive interface between social structures and discourse structures. Within these views, whenever social groups, including the producers of antipoligamy texts, voice their ideas and feelings, their ideology come up apparently or, otherwise, lies behind language. This paper is an attempt to explain how women formulate their beliefs into a joint statement: by using what ideological discourse production strategies they share their ideology to public. A Joint Statement issued in December 2006, which contains a broad definition of poligamy in negative sense, in fact represents negative other-representation strategy used by its producer.